Phraseology as a medium for expressing stereotypical views of the others: The case of English and Slovene idioms with ethnonyms - Vrbinc, Alenka; Vrbinc, Marjeta (Slovenski jezik / Slovene Linguistic Studies, 2023)
The article deals with national stereotypes found in English and Slovene onomastic idioms containing ethnonyms or their derivatives. The aim is to address the reasons why stereotypical views of other nations emerged in a certain period of time in English and Slovene. On the basis of concrete examples, the (predominantly negative) connotations of idioms are explained. It can be claimed that the English idioms with ethnonyms reflect the historical relations of the English with other (mostly European) nations regarded by the English as their enemies or rivals. The Slovene idioms with ethnonyms may be a result of calquing from German or they may reflect the stereotypical images Slovenes (have) had of other nations; they, however, do not reflect rivalry between Slovenes and other nations.